1988
DOI: 10.1177/096032718800700207
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal Aberrations and Sister Chromatid Exchanges in Lymphocytes and Urine Mutagenicity of Migraine Patients: A Comparison of Chronic Feverfew Users and Matched Non-users

Abstract: 1 Thirty migraine patients who had taken the leaves, tablets or capsules of feverfew daily for more than 11 consecutive months were compared to 30 feverfew non-user migraine patients who had been individually age- and sex-matched. 2 The frequency of chromosomal aberrations and sister chromatid exchanges (SCE) were determined from lymphocyte cultures established from blood samples taken over a period of several months. Matched pairs were sampled on the same date for two-thirds of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 17 publications
(5 reference statements)
0
4
0
Order By: Relevance
“…How safe is feverfew? Chronic prophylactic use of feverfew did not affect the frequency of chromosomal aberration in lymphocytes or urine mutagenicity 27 . Anecdotal reports relate to contact dermatitis (e.g.…”
Section: Discussionmentioning
confidence: 81%
“…How safe is feverfew? Chronic prophylactic use of feverfew did not affect the frequency of chromosomal aberration in lymphocytes or urine mutagenicity 27 . Anecdotal reports relate to contact dermatitis (e.g.…”
Section: Discussionmentioning
confidence: 81%
“…No studies of chronic toxicity have been performed on the plant and the safety of long-term use has not been established (Ernst & Pittler, 2000). However, a toxicity study has shown that chronic use of feverfew does not affect the frequency of chromosomal aberration in lymphocytes or urine mutagenicity (Anderson et al, 1988). Feverfew can affect the hepatic metabolism of medications, including those used to treat migraine, and may have anticoagulant properties (Losche et al, 1987;Miller, 1998).…”
Section: Study Selectionmentioning
confidence: 99%
“…Analysis of the frequency of chromosomal aberrations and sister chromatid exchanges in circulating lymphocytes from patients who ingested feverfew for 11 months found no unexpected aberrations, suggesting that the plant does not induce chromosomal abnormalities. [62]…”
Section: Toxicologymentioning
confidence: 99%